Anxiety Factors of Nursing Department Students Conducting Online Learning During the 2020 Pandemic - Lailatul Fadilah; Rohanah Rohanah (Politeknik Kesehatan Kementerian Kesehatan Banten, 2023)
The Covid-19 pandemic is a non-natural disaster that not only affects physical health but also has an impact on the mental and psychological health of the community. Disturbed psychological conditions can affect the immunity of the human body to fight viruses, as well as the ability to think clearly so that they cannot pay attention to a healthy lifestyle. Students in higher education are also feeling the impact and consequences of COVID-19. Unpreparedness and confusion of students in taking part in online lectures along with a pile of assignments can cause anxiety, especially during the pandemic. Anxiety in students with distance learning, especially with the covid-19 pandemic, can cause ongoing anxiety and impact student achievement and the inability of students to fulfill their roles and obligations if they are not immediately controlled and handled. This study used a cross-sectional design, with the aim of knowing the anxiety factors of students during the pandemic in 2020. The study was conducted in October - December 2020 with a population of students from the Tangerang Nursing Department, Poltekkes Kemenkes Banten. The sampling method used was simple random sampling totaling 93 people. The results showed that fewer than some respondents experienced anxiety 25 respondents (26.9%), and the statistical test analysis showed that domicile, lecture assignments, physical distancing, and lecture facilities had no significant relationship with student anxiety in learning during the pandemic.